Spatially gifted, academically inconvenienced: Spatially talented students experience less academic engagement and more behavioural issues than other talented students. (17th February 2020) - Lakin, Joni M.; Wai, Jonathan
Abstract : Background: Spatially talented students have a capacity for success that is too often overlooked by educational services. Because these students may lack appropriate challenge, theorists suggest these students experience greater academic struggles than other gifted students, including behavioural problems and lack of academic engagement. Aims: The goal of this research was to explore empirical evidence for the claim that spatially talented students would experience more academic struggles than other gifted students. We sought to understand the size of the 'spatially talented' population and their patterns of behavioural and academic struggles in high school. We also looked at long‐term outcomes, including degree completion. Samples: This article explores characteristics of spatial talent in three US nationally representative data sets: Project Talent (1960), High School and Beyond (1980), and the National Longitudinal Study of Youth (1997). Combined, these data provide a 60‐year longitudinal study of student outcomes. Methods: This study utilized factor analysis, analysis of variance (ANOVA), and regression methods to explore the research questions for each data set. Results and Conclusions: From our analyses, we estimate that 4–6% (at least 2 million) of the 56.6 million students in the US K‐12 system are spatially talented students that are not identified by common gifted and talented screening processes. These students had greater academic challenges, including reading difficulties, poor study habits, and behavioural troubles. We also found that spatially talented students were less likely to complete college degrees compared to other talented students. Our findings support the need for greater services to these talented students.